Stellar laboratories: IX. New Se V, Sr IV - VII, Te VI, and I VI oscillator strengths and the Se, Sr, Te, and I abundances in the hot white dwarfs G191-B2B and RE 0503-289 - Rauch, Thomas; Demleitner, Markus (Arxiv, 2017)
To analyze spectra of hot stars, advanced non-local thermodynamic equilibrium (NLTE) model-atmosphere techniques are mandatory. Reliable atomic data is for the calculation of such model atmospheres. We aim to calculate new Sr IV - VII oscillator strengths to identify for the first time Sr spectral lines in hot white dwarf (WD) stars and to determine the photospheric Sr abundances. o measure the abundances of Se, Te, and I in hot WDs, we aim to compute new Se V, Te VI, and I VI oscillator strengths. To consider radiative and collisional bound-bound transitions of Se V, Sr IV - VII, Te VI, and I VI in our NLTE atmosphere models, we calculated oscillator strengths for these ions. We newly identified four Se V, 23 Sr V, 1 Te VI, and three I VI lines in the ultraviolet (UV) spectrum of RE0503-289. We measured a photospheric Sr abundance of 6.5 +3.8/-2.4 x 10**-4 (mass fraction, 9500 - 23800 times solar). We determined the abundances of Se (1.6 +0.9/-0.6 x 10**-3, 8000 - 20000), Te (2.5 +1.5/-0.9 x 10**-4, 11000 - 28000), and I (1.4 +0.8/-0.5 x 10**-5, 2700 - 6700). No Se, Sr, Te, and I line was found in the UV spectra of G191-B2B and we could determine only upper abundance limits of approximately 100 times solar. All identified Se V, Sr V, Te VI, and I VI lines in the UV spectrum of RE0503-289 were simultaneously well reproduced with our newly calculated oscillator strengths.
Gesehen am 26.03.2018